TEORI DAN MODEL PENGEMBANGAN KURIKULUM DI INDONESIA - Fiska, Dewi (Ensiklopedia Education Review, 2024)
Curriculum development is always carried out by the world of education in accordance with the demands of technological developments and population dynamics carried out by an educational institution. Curriculum development is usually carried out by the Government in general, and by a school that wants to improve the quality of the educational institution itself. In curriculum development, what must be considered first is the terminology in the curriculum itself. According to Dakir in his book Curriculum Planning and Development states: "The curriculum terminology includes: (1). Core Curriculum, core means core, in the curriculum means learning experiences that must be provided both in the form of individual needs and general needs. (2). Hidden Curriculum means that the curriculum is hidden. What does hidden mean? Hidden means invisible but not lost. So this hidden curriculum is not planned, not programmed and not designed but has an influence either directly or indirectly on the output of the teaching and learning process. The curriculum development itself has various definitions. In accordance with the opinions of experts such as: "Curriculum development according to Suparlan is the process of planning and compiling curriculum by curriculum developers and activities carried out so that the resulting curriculum can become teaching materials and references used to achieve educational goals.